The image of the map between reality and vision (Bulletin KNOB, 1989)
The Fourth Note about area planning to direct the Dutch spatial policy appeared in 1988. Parts A and D of this Note contain special maps which point out the note's background, a map of NW-Europe the author made forming one of these. The level of scale of these maps is higher than usual at Dutch area planning. Purpose of the Fourth Note is to promote such spatial and ecological conditions that individual and collective strivings in society show to full advantage and to reassure the diversity, coherence and durability of the physical environment. Area planning always is making choices; it is normative just like the maps reflecting future policy. The concreteness of these maps is determined by the level of the used scale, 1:1000 f.e., making a reasonably detailed town-planning design possible, but the map of NW-Europe drawn by the author has a scale of 1:500.000! Topographical maps with no smaller scale than 1:50.000 are often used as basis for the future town-planning design. The larger the scale of the area planning-map, the closer the plan stays at reality. The map of NW-Europe seems far from reality although we are able to recognize its symbols like towns, woods, water or mountains. This current language of topographical maps does not count for the area planning-maps because on this field choices have to be made about WHAT and HOW one wants to show something. The first integral plan for Holland is the Second Note about area planning (1966). Little squares point the possible development of the urban landscape, the green recreation areas forming a second element on behalf of Holland's increasing population. The structural sketch of the Urbanization Note as part of the Third Note on area planning (1976) has a broader and therefore clearer character than the Second Note only indicating elements for the future policy. In 1983 this sketch has been adapted and for the first time symbols are used to represent urban areas. The descended trust in the ability to 'make' Holland led to the very abstract rendering of the Integration-map Fourth Note. Executed in a different level of scale the symbols almost totally cover Holland. They can only be understood by specialists and exclusively serve as reference to aims and desirable developments. The map of NW-Europe had to show how the proposed spatial development would conform to NW-Europe. The Dutch policy forms point of departure whereby the spatial main structure, analysis of the existing situation and spatial development perspectives are rendered. Very difficult was the translation of the spatial development perspectives to notions that could analyze the foreign situation, because of course only choices of the Dutch policy are reflected. Although the map is no more than indicative it has not only proved to be inspiring for the thinking about Dutch developments but also that area planning on an European scale is possible. The articles about nature and landscape in the border areas as these are published in the Annual of the State Planning Office show another approach to international developments. The design-map is a thematic one indicating how overstepping area planning could lead to a better connection between till now isolated nature-areas. Thus topographical maps describe reality. They know a large measure of unity at the reproduction and are confined in scale. Mostly aiming at the future area planning-maps depart from a certain vision. They are normative with symbols rendering notions. Therefore they know a large variety in design and prevail in each scale.